Formulation And Effectiveness Of Bulung Sangu (Gracilaria Gracilis) Scrub For Skin Moisturization And Brightening - Simarmata, Jonatan Alexius; Wirawan, I Gede Putu; Pranatayana, Ida Bagus Gede (Ridwan Institute, 2025)
Free radicals (UV rays). Therefore, the best solution is needed by using skincare products containing antioxidants. Antioxidants can neutralize free radicals from UV rays. The hallmark of a product attracts people to buy, try, or feel the benefits of skincare ingredients. This research is experimental to determine the effectiveness of ingredients from bulung sangu, which are formulated in the form of fine powder for skincare. The study used four scrub samples, namely bulung sangu (Formulation 1 dan 2), without bulung sangu (Formulation 3), and Bali Alus Seaweed (Formulation 4) which were used for 2 weeks by 30 panelists from the Faculty of Agriculture, Udayana University with hedonic tests for appearance, aroma, color, and texture of the scrub and tests the effectiveness of moisture and brightness to the skin. The results obtained, Formulation 4, the highest average value and total percentage of hedonic (78%, 79%, 81%, 83%) and Formulation 2, the lowest average value and total percentage of hedonic (64%, 56%, 63%, 61%). The results of the effectiveness test Formulation 1 have the highest value, namely skin moisture normal to slightly moist (38% to 46%) and tanned skin to bright white skin (15 to 9). Meanwhile, Formulation 4 from Bali Alus Seaweed, have the lowest value, namely skin moisture normal to slightly moist (41% to 44%) and the skin remains in the tanned skin (15). This is caused by several factors, gene experession, environment, activity and physical condition, and the effectiveness of the preparation of scrub product ingredients.